Growth, Intellectual Capital, Financial Performance And Firm Value : Evidence From Indonesia Automotive Firms - Johanda Putri, Indah Ayu; Budiyanto, Budiyanto; Triyonowati, Triyonowati; Ilham, Ilham (International Journal of Science, Technology & Management, 2023)
This study analyzes and explains empirical evidence of the effect of growth and Intellectual Capital respectively on financial performance and firm value, as well as the role of Financial Performance in mediating the influence of company growth and Intellectual Capital respectively on firm value. The benefits of this research are expected to be a reference that enriches the literature of Management Science, especially related to signaling theory and Resource Based Theory. In addition, this research is expected to provide benefits for automotive company managers in developing strategies that can improve financial performance and firm value, investors in automotive companies in making the right decisions in investing in automotive companies and the government in formulating policies related to automotive companies so that more investors invest in automotive companies. To test the hypothesis used Partial Least Square (PLS) analysis. The results of the hypothesis test show that: (1) the company's growth has a positive and insignificant effect on financial performance, (2) Intellectual Capital has a positive and significant effect on financial performance, (3) company growth has a positive and insignificant effect on firm value, (4) Intellectual Capital has a positive and insignificant effect on firm value, (5) financial performance has a positive and significant effect on firm value, (6) financial performance does not mediate the company's growth to the company's value and (7) financial performance mediates Intellectual Capital to the value of the company